How Does the Progressivity of Taxes and Government Transfers Impact People’s Willingness to Pay Tax? : Experimental Evidence across Developing Countries - Hoy, Christopher (World Bank, Washington, DC, 2022)
This paper examines how the progressivity of taxes and government transfers impacts people’s willingness to pay tax through a randomized survey experiment with over 30,000 respondents across eight developing countries. Respondents increased (decreased) their willingness to pay taxes when they received accurate information that taxes in their country are progressive (not progressive). These effects were predominantly driven by respondents in cases where the information they received was counter to their prior beliefs and/or consistent with their preferences. These results suggest changes in policies that increase (decrease) the progressivity of tax systems may also lead to increases (decreases) in tax compliance.